Non-oriented electromagnetic steel sheet and method for manufacturing the same

CN120693420BActive Publication Date: 2026-09-25NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202480012932.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-02-15
Filing Date
2024-02-15
Publication Date
2026-09-25
Estimated Expiration
2044-02-15

AI Technical Summary

Technical Problem

然而,准备2个种类的无取向电磁钢板会使铁芯的制造工序变得麻烦,并且会招致成品率的降低

Benefits of technology

[0063]根据本发明,能够稳定地得到具有高强度及优异的磁特性的无取向电磁钢板。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005549707800000171
    Figure BDA0005549707800000171
  • Figure BDA0005549707800000181
    Figure BDA0005549707800000181
Patent Text Reader

Abstract

A non-oriented electrical steel sheet, a chemical composition of a base material of which is, in mass%, C: 0.0040% or less, Si: more than 3.50% and 4.50% or less, Mn: less than 0.60%, Al: 0.30 to 0.90%, P: 0.030% or less, S: 0.0018% or less, N: 0.0040% or less, Ti: less than 0.0040%, Nb: less than 0.0050%, Zr: less than 0.0050%, V: less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, a total of one or both of Sn and Sb: 0.005 to 0.060%, a remainder: Fe and impurities, satisfies [4.2 ≤ Si + Al + 0.5 × Mn ≤ 4.9], an average crystal grain diameter of the base material is 10 to 40 μm, a concentration of {111} <112> orientation is 8.0 or less, and a sheet thickness of the base material is 0.10 to 0.30 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a non-oriented electromagnetic steel sheet and its manufacturing method. Background Technology

[0002] In recent years, global environmental issues have garnered significant attention, leading to a growing demand for energy conservation. Among these demands is a strong expectation for increased efficiency in electronic devices. Consequently, the requirements for improving the magnetic properties of non-oriented electromagnetic steel sheets, widely used as core materials in motors and generators, are intensifying. This trend is particularly pronounced in drive motors for electric and hybrid vehicles, as well as motors for air conditioning compressors. Furthermore, the expectation for miniaturized and efficiently high-output drive motors and compressor motors is also strengthening.

[0003] To achieve high efficiency in electric motors, reducing iron losses and copper losses, which are the main sources of losses, is crucial. For reducing iron losses, improving the iron loss of the electromagnet used in the motor core is effective; for reducing copper losses, increasing the magnetic flux density of the electromagnet is effective. On the other hand, to achieve high output in electric motors, high torque and high-speed rotation are important. For high torque, increasing the magnetic flux density of the electromagnet is effective; for high-speed rotation, increasing the strength of the electromagnet is effective. Therefore, to promote high efficiency and high output in electric motors, electromagnets with low iron losses, high magnetic flux density, and high strength are needed.

[0004] As described above, the motor core of various motors consists of a stator as a stationary component and a rotor as a rotating component. The required characteristics of the stator and rotor constituting the motor core are not the same. For the stator, excellent magnetic properties (low iron loss and high magnetic flux density) are required, while for the rotor, low iron loss and excellent mechanical properties (high strength) are required.

[0005] Because the stator and rotor require different characteristics, the desired characteristics can be achieved by manufacturing separate non-oriented electromagnetic steel sheets for the stator and rotor. However, preparing two types of non-oriented electromagnetic steel sheets complicates the core manufacturing process and reduces the yield. Therefore, in order to achieve the low iron loss and high strength required for the rotor, and the low iron loss and high magnetic flux density required for the stator, a non-oriented electromagnetic steel sheet with excellent strength and magnetic properties has been continuously researched.

[0006] For example, in patent documents 1-4, an attempt was made to achieve high strength and excellent magnetic properties.

[0007] Prior technology documents

[0008] Patent documents

[0009] Patent Document 1: International Publication No. 2019 / 017426

[0010] Patent Document 2: International Publication No. 2020 / 091039

[0011] Patent Document 3: International Publication No. 2021 / 210672

[0012] Patent Document 4: Japanese Patent Application Publication No. 2010-90474 Summary of the Invention

[0013] The technical problem that the invention aims to solve

[0014] However, in order to achieve non-oriented electromagnetic steel sheets that balance high strength and low iron loss, as disclosed in Patent Documents 1-4, it is necessary to contain a large amount of alloying elements, which leads to problems such as reduced toughness and easy breakage during cold rolling.

[0015] This invention was made to solve such problems, and its purpose is to stably provide a non-oriented electromagnetic steel sheet with high strength and excellent magnetic properties.

[0016] Technical means for solving technical problems

[0017] The present invention relates to the following non-oriented electromagnetic steel sheet and its manufacturing method.

[0018] (1) A non-oriented electromagnetic steel sheet, wherein the chemical composition of its base material is expressed as mass %

[0019] C: Below 0.0040%,

[0020] Si: exceeding 3.50% but below 4.50%,

[0021] Mn: less than 0.60%,

[0022] Al: 0.30–0.90%,

[0023] P: below 0.030%,

[0024] S: Below 0.0018%,

[0025] N: below 0.0040%,

[0026] Ti: less than 0.0040%,

[0027] Nb: less than 0.0050%,

[0028] Zr: less than 0.0050%,

[0029] V: less than 0.0050%,

[0030] Cu: less than 0.200%,

[0031] Ni: less than 0.500%,

[0032] The total of one or two of Sn and Sb: 0.005% to 0.060%.

[0033] Remaining components: Fe and impurities.

[0034] And satisfy the following equation (i),

[0035] 4.2≤Si+Al+0.5×Mn≤4.9…(i)

[0036] In the above formula, the element symbols represent the content (mass%) of each element.

[0037] The average crystal grain size of the parent material is 10–40 μm.

[0038] {111} is located at a position 1 / 4 of the plate thickness from the surface of the base material. <112> The degree of aggregation of orientation is below 8.0.

[0039] The thickness of the base material is 0.10 to 0.30 mm.

[0040] (2) The non-oriented electromagnetic steel sheet as described in (1) above, wherein the tensile strength is 650 MPa or above.

[0041] (3) The non-oriented electromagnetic steel sheet as described in (1) or (2) above, wherein an insulating film is provided on the surface of the base material.

[0042] (4) A method for manufacturing a non-oriented electromagnetic steel sheet, comprising the following steps performed on a steel ingot: a hot rolling process; a hot-rolled sheet annealing process with a homogenization temperature of 800-920°C and a homogenization time of 1 second-10 minutes; a descaling process by pickling after shot peening; a cold rolling process to a sheet thickness of 0.10-0.30 mm; and a final annealing process by heating the ingot to a temperature of 850°C or higher but less than 900°C at a heating rate of 400°C / s or higher in a temperature range of 500-850°C, and then cooling the ingot at a holding time of 20 seconds or less at 850°C or higher.

[0043] The steel ingot has the following chemical composition, in mass percent:

[0044] C: Below 0.0040%,

[0045] Si: exceeding 3.50% but below 4.50%,

[0046] Mn: less than 0.60%,

[0047] Al: 0.30–0.90%,

[0048] P: below 0.030%,

[0049] S: Below 0.0018%,

[0050] N: below 0.0040%,

[0051] Ti: less than 0.0040%,

[0052] Nb: less than 0.0050%,

[0053] Zr: less than 0.0050%,

[0054] V: less than 0.0050%,

[0055] Cu: less than 0.200%,

[0056] Ni: less than 0.500%,

[0057] The total of one or two of Sn and Sb: 0.005% to 0.060%.

[0058] Remaining components: Fe and impurities.

[0059] And satisfy the following equation (i),

[0060] 4.2≤Si+Al+0.5×Mn≤4.9…(i)

[0061] In the above formula, the element symbols represent the content (mass%) of each element.

[0062] Invention Effects

[0063] According to the present invention, non-oriented electromagnetic steel sheets with high strength and excellent magnetic properties can be stably obtained. Detailed Implementation

[0064] In order to solve the above problems, the inventors conducted in-depth research and obtained the following understanding.

[0065] To ensure toughness during cold rolling and obtain non-oriented electromagnetic steel sheets with low iron loss, high magnetic flux density, and high strength, the content of Si, Mn, and Al, the main alloying elements, needs to be optimized.

[0066] Specifically, the Si content, which maximizes solid solution strengthening and contributes most to increasing electrical resistance, is between 3.50% and 4.50%. Furthermore, to improve grain growth and stably obtain excellent magnetic properties, the Al content is 0.30% or higher. On the other hand, to suppress toughness degradation, the Al content is set to 0.90% or lower.

[0067] Furthermore, Mn has the lowest solid solution strengthening ability among the three elements, but suffers less toughness degradation and contributes to increased electrical resistance. However, through repeated research, the inventors have found that when Mn, which has a lower solid solution strengthening ability compared to Si and Al, is present in excess, the decrease in magnetic flux density is more significant than the increase in strength. At high Mn contents, it becomes difficult to stably improve magnetic properties. Therefore, the Mn content is set to be less than 0.60%.

[0068] In the manufacturing process of non-oriented electromagnetic steel sheets, hot-rolled sheet annealing is generally performed before cold rolling. However, when the Si content in the steel sheet is high and the sheet thickness needs to be reduced to decrease iron loss, it is preferable to lower the soaking temperature during hot-rolled sheet annealing to suppress defects such as sheet breakage and edge cracking during cold rolling. On the other hand, it is known that the higher the soaking temperature during hot-rolled sheet annealing, the higher the magnetic flux density will be; therefore, lowering the soaking temperature will lead to a decrease in magnetic flux density.

[0069] Therefore, the inventors have studied a method for reducing the homogenization temperature during annealing of hot-rolled steel sheets while increasing magnetic flux density. As a result, it was discovered that by rapidly heating during the final annealing after cold rolling, the development of textures detrimental to magnetic properties can be suppressed, and the decrease in magnetic flux density can be suppressed even when the homogenization temperature during annealing of hot-rolled steel sheets is relatively low.

[0070] Furthermore, the inventors conducted experiments involving rapid heating to various temperatures. The results showed that even with rapid heating, the temperature reached was relatively low, and no improvement in magnetic properties was observed. However, by rapidly heating to temperatures above 850°C, the magnetic properties were improved.

[0071] Furthermore, by suppressing the temperature to below 900°C and shortening the time spent in the temperature range above 850°C, the grains can be refined, ensuring the predetermined magnetic properties and improving the strength.

[0072] This invention is based on the above understanding. The following is a detailed description of each element of this invention.

[0073] 1. Overall Composition

[0074] The non-oriented electromagnetic steel sheet of one embodiment of the present invention has high strength and excellent magnetic properties, and is therefore suitable for both stators and rotors. Furthermore, it is preferable that the non-oriented electromagnetic steel sheet of this embodiment has an insulating film on the surface of the base material described below.

[0075] 2. Chemical composition of the parent material

[0076] The reasons for the limitations of each element are as follows. Additionally, in the following explanation, "%" for content means "mass %".

[0077] C: Below 0.0040%

[0078] Carbon (C) is an element that causes deterioration of iron losses in non-oriented electromagnetic steel sheets. When the C content exceeds 0.0040%, the iron losses of the non-oriented electromagnetic steel sheet deteriorate, and good magnetic properties cannot be obtained. Therefore, the C content is set to 0.0040% or less. Preferably, the C content is 0.0035% or less, and more preferably, 0.0030% or less. In addition, C contributes to the high strength of non-oriented electromagnetic steel sheets; therefore, to obtain this effect, it is preferable that the C content is 0.0005% or more, and more preferably, 0.0010% or more.

[0079] Si: Above 3.50% and below 4.50%

[0080] Silicon (Si) is an element that increases the electrical resistance of steel, thereby reducing eddy current losses and improving the iron loss of non-oriented electromagnetic steel sheets. Furthermore, Si has a high solid solution strengthening ability, making it effective for increasing the strength of non-oriented electromagnetic steel sheets. To achieve these effects, the Si content is set to be more than 3.50%. Preferably, the Si content is 3.60% or more, more preferably 3.70% or more, and even more preferably 3.80% or more. On the other hand, when the Si content is excessive, the processability deteriorates significantly, making cold rolling difficult. Therefore, the Si content is set to 4.50% or less. Preferably, the Si content is 4.40% or less, more preferably 4.30% or less.

[0081] Mn: less than 0.60%

[0082] Manganese (Mn) is an effective element for increasing the electrical resistance of steel, reducing eddy current losses, and improving the iron loss of non-oriented electromagnetic steel sheets. However, because Mn has a weaker solid solution strengthening ability compared to Si and Al, a large content is required to obtain high strength, which leads to a greater decrease in magnetic flux density. Therefore, the Mn content is set to less than 0.60%. Preferably, the Mn content is 0.55% or less, more preferably 0.50% or less. While a lower limit for the Mn content is not required, it is preferable to set the Mn content to 0.10% or more, more preferably 0.20% or more, to achieve the aforementioned effects.

[0083] Al: 0.30–0.90%

[0084] Al (aluminum) is an element that reduces eddy current losses and improves iron loss in non-oriented electromagnetic steel sheets by increasing the electrical resistance of steel. Furthermore, while not as potent as Si, Al contributes to the high strength of non-oriented electromagnetic steel sheets through solid solution strengthening. Moreover, the addition of an appropriate amount of Al suppresses the refinement of AlN formed by bonding with N in the steel, improving grain growth during final annealing. To achieve these effects, the Al content is set to 0.30% or more. Preferably, the Al content is 0.40% or more, more preferably, more than 0.45%, and even more preferably, 0.50% or more. On the other hand, when the Al content is excessive, toughness deteriorates and the risk of fracture during cold rolling increases. Therefore, the Al content is set to 0.90% or less. Preferably, the Al content is 0.80% or less, more preferably, 0.70% or less.

[0085] In this embodiment, the resistivity of the steel is ensured by appropriately controlling the contents of Si, Al, and Mn. Furthermore, from the viewpoint of ensuring strength, it is also necessary to appropriately control the contents of Si, Al, and Mn. On the other hand, from the viewpoint of ensuring magnetic flux density and toughness, an upper limit is also required. Therefore, the contents of Si, Al, and Mn are respectively within the aforementioned ranges, and furthermore, the following formula (i) needs to be satisfied. Regarding the intermediate value of the following formula (i), it is preferably 4.3 or more, more preferably 4.4 or more, more preferably 4.8 or less, and more preferably 4.7 or less.

[0086] 4.2≤Si+Al+0.5×Mn≤4.9…(i)

[0087] In the above formula, the element symbols represent the content (mass%) of each element.

[0088] P: below 0.030%

[0089] Phosphorus (P) is contained in steel as an impurity, and when its content is excessive, the toughness of the non-oriented electromagnetic steel sheet will be significantly reduced. Therefore, the P content is set to 0.030% or less. Preferably, the P content is 0.025% or less, and more preferably, 0.020% or less. In addition, extremely low P content can sometimes lead to increased manufacturing costs, so preferably, the P content is 0.003% or more, and more preferably, 0.005% or more.

[0090] S: below 0.0018%

[0091] Sulfur (S) is an element that increases iron loss and degrades the magnetic properties of non-oriented electromagnetic steel sheets by forming fine precipitates of MnS. Therefore, the S content is set to 0.0018% or less. Preferably, the S content is 0.0016% or less, more preferably 0.0014% or less. In addition, extremely low S content can sometimes lead to increased manufacturing costs, so preferably, the S content is 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0092] N: below 0.0040%

[0093] Nitrogen (N) is an element that inevitably mixes into steel. It forms nitrides, increasing iron loss and deteriorating the magnetic properties of non-oriented electromagnetic steel sheets. Therefore, the N content is set to 0.0040% or less. Preferably, the N content is 0.0030% or less, and more preferably 0.0020% or less. Furthermore, drastic reductions in the N content can sometimes increase manufacturing costs; therefore, it is preferable that the N content is 0.0005% or more.

[0094] Ti: less than 0.0040%

[0095] Titanium (Ti) is an element that inevitably mixes into steel and can combine with carbon or nitrogen to form precipitates (carbides, nitrides). When carbides or nitrides form, these precipitates themselves degrade the magnetic properties of the non-oriented electromagnetic steel sheet. Furthermore, they hinder grain growth during final annealing, further degrading the magnetic properties of the non-oriented electromagnetic steel sheet. Therefore, the Ti content is set to less than 0.0040%. Preferably, the Ti content is 0.0030% or less, more preferably 0.0025% or less. Additionally, drastic reductions in the Ti content can sometimes increase manufacturing costs; therefore, it is preferable that the Ti content is 0.0005% or more.

[0096] Nb: less than 0.0050%

[0097] Niobium (Nb) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electromagnetic steel sheets. Therefore, the Nb content is set to less than 0.0050%. Preferably, the Nb content is 0.0040% or less, more preferably 0.0030% or less, and even more preferably 0.0020% or less. In addition, extremely low Nb content can sometimes lead to increased manufacturing costs, so it is preferable that the Nb content is 0.0001% or more.

[0098] Zr: less than 0.0050%

[0099] Zirconium (Zr) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electromagnetic steel sheets. Therefore, the Zr content is set to less than 0.0050%. Preferably, the Zr content is 0.0040% or less, more preferably 0.0030% or less, and even more preferably 0.0020% or less. In addition, extremely low Zr content can sometimes lead to increased manufacturing costs, so it is preferable that the Zr content is 0.0001% or more.

[0100] V: Less than 0.0050%

[0101] Vanadium (V) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electromagnetic steel sheets. Therefore, the V content is set to less than 0.0050%. Preferably, the V content is 0.0040% or less, more preferably 0.0030% or less, and even more preferably 0.0020% or less. In addition, extremely low V content can sometimes lead to increased manufacturing costs, so it is preferable that the V content is 0.0001% or more.

[0102] Cu: less than 0.200%

[0103] Copper (Cu) is an element that inevitably mixes into steel. Intentionally including Cu increases the manufacturing cost of non-oriented electromagnetic steel sheets. Therefore, in this embodiment, it is not necessary to actively include Cu; the impurity level is sufficient. The Cu content is set to be less than the maximum value that can inevitably be mixed in during the manufacturing process, i.e., 0.200%. Preferably, the Cu content is 0.150% or less, more preferably 0.100% or less. Furthermore, the lower limit of the Cu content is not particularly limited, but drastic reductions in Cu content can sometimes increase manufacturing costs. Therefore, preferably, the Cu content is 0.001% or more, more preferably 0.003% or more, and even more preferably 0.005% or more.

[0104] Ni: less than 0.500%

[0105] Ni (Ni) is an element that inevitably mixes into steel. However, Ni is also an element that increases the strength of non-oriented electromagnetic steel sheets and can be intentionally included. However, Ni is expensive, so the Ni content is set to less than 0.500%. Preferably, the Ni content is 0.400% or less, more preferably 0.300% or less. Furthermore, the lower limit of the Ni content is not particularly limited, but drastic reductions in Ni content can sometimes increase manufacturing costs. Therefore, preferably, the Ni content is 0.001% or more, more preferably 0.003% or more, and even more preferably 0.005% or more. Moreover, when intentionally included, it is preferable to set the Ni content to 0.200% or more.

[0106] The total of one or two of Sn and Sb: 0.005% to 0.060%

[0107] Sn (tin) and Sb (antimony) improve the texture and increase the magnetic flux density of non-oriented electromagnetic steel sheets. Furthermore, they are also useful elements for ensuring low iron loss in non-oriented electromagnetic steel sheets by segregating on the surface of the base material and suppressing oxidation and nitriding during annealing. To obtain these effects, the total content of one or both of Sn and Sb is set to 0.005% or more. Preferably, the total content is 0.010% or more, and more preferably, 0.015% or more. On the other hand, when the total content of Sn and Sb is excessive, the toughness of the steel decreases and cold rolling becomes difficult. Therefore, the total content of one or both of Sn and Sb is set to 0.060% or less. Preferably, the total content is 0.050% or less, and more preferably, 0.040% or less.

[0108] In the chemical composition of the base material of the non-oriented electromagnetic steel sheet of the present invention, the remaining part is Fe and impurities. Here, "impurities" means components that may be mixed in during the industrial manufacturing of steel due to various reasons such as raw materials such as ore and waste, and manufacturing processes. Such components are permissible to the extent that they do not adversely affect the present invention.

[0109] Furthermore, the contents of Cr and Mo, as impurity elements, are not specifically specified. In the non-oriented electromagnetic steel sheet of this embodiment, even if these elements are present in the range of 0.5% or less, it will not have a significant impact on the properties of the non-oriented electromagnetic steel sheet of this embodiment. Furthermore, even if Ca and Mg are present in the range of 0.002% or less, it will not have a significant impact on the properties of the non-oriented electromagnetic steel sheet of this embodiment. Even if rare earth elements (REM) are present in the range of 0.004% or less, it will not have a significant impact on the properties of the non-oriented electromagnetic steel sheet of this embodiment. In this embodiment, REM refers to a total of 17 elements consisting of Sc, Y, and lanthanides, and the aforementioned REM content refers to the total content of these elements.

[0110] O is also an impurity element, but even if it is present in the range of 0.035% or less, it will not affect the properties of the non-oriented electromagnetic steel sheet of this embodiment. O may also be mixed into the steel during the annealing process, so even if it is present in the slab stage (i.e., ladle value) in the range of 0.010% or less, it will not have a particular effect on the properties of the non-oriented electromagnetic steel sheet of this embodiment.

[0111] In addition to the elements mentioned above, elements such as Zn, Pb, Bi, As, B, and Se may also be included as impurity elements. However, when their respective contents are in the range of 0.0050% or less, they will not impair the characteristics of the non-oriented electromagnetic steel sheet of this embodiment.

[0112] The chemical composition of the base material of the non-oriented electromagnetic steel sheet of this embodiment can be determined using various known methods. For example, it can be determined using ICP luminescence analysis, gravimetric analysis, or spark discharge luminescence analysis. Furthermore, C and S can be determined using combustion-infrared absorption method, N can be determined using inert gas combustion-thermal conduction method, and O can be determined using inert gas melting-non-dispersive infrared absorption method.

[0113] 3. Crystal grain size

[0114] In this embodiment, the average grain size of the base material is set to 10–40 μm. By setting the average grain size of the base material to 10 μm or more, the deterioration of hysteresis loss can be suppressed, and the magnetic properties can be improved. On the other hand, by setting the average grain size to 40 μm or less, the strength of the steel can be improved. Preferably, the average grain size is 12 μm or more, more preferably 14 μm or more. Furthermore, preferably, the average grain size is 38 μm or less, more preferably 36 μm or less.

[0115] In addition, in this invention, the average grain size of the base material is determined according to JIS G 0551:2020 "Microscopic test method for grain size of steel".

[0116] 4. Texture

[0117] In this embodiment, the development of textures that degrade magnetic properties is suppressed. Specifically, {111} <112> The aggregation degree of orientation is set below 8.0. This is achieved by suppressing {111} <112> A well-developed orientation can improve magnetic properties. Preferably, {111} <112> The degree of aggregation of the orientation is 7.5 or less, more preferably 7.0 or less. For {111} <112> No lower limit needs to be set for the clustering degree of orientation, but 1.0 will be the de facto lower limit.

[0118] Additionally, {111} <112> The degree of aggregation of orientation was determined using an X-ray diffraction apparatus. Furthermore, the degree of aggregation refers to the value obtained by measuring the X-ray intensity of a standard sample and the test material that do not exhibit aggregation towards a specific orientation using X-ray diffraction under the same conditions, and dividing the X-ray intensity of the test material by the X-ray intensity of the standard sample. The specific measurement method is as follows. The measurement was performed on the surface after the base material of the non-oriented electromagnetic steel sheet of the test material was removed by chemical grinding from one side surface to a depth of 1 / 4 of the sheet thickness. The {200} plane, {110} plane, and {310} plane of the α-Fe phase were determined using an X-ray diffraction apparatus.

[0119] The pole plots of the {211} plane are used to determine the {111} plane. The {211} plane is obtained from the crystal orientation distribution function (ODF) representing the three-dimensional texture calculated using series expansion. <112> The degree of aggregation of orientations. This will be displayed in the ODF file. At Φ = 55° of the cross section The clustering degree is defined as {111} <112> The degree of clustering of orientations.

[0120] 5.Magnetic properties

[0121] In the non-oriented electromagnetic steel sheet of this embodiment, the term "excellent magnetic properties" means that the iron loss W 10 / 400 Lower, magnetic flux density B 50 Relatively high.

[0122] Here, the magnetic properties (iron loss W) are made possible. 10 / 400 and magnetic flux density B 50 The density of the steel plate was determined according to the Epstein test method specified in JIS C 2550-1:2011. Furthermore, the density of the steel plate was set to 7.65 g / cm³. 3 To perform magnetic measurements. Additionally, iron loss W 10 / 400This means that the iron loss generated under conditions such as a maximum magnetic flux density of 1.0T and a frequency of 400Hz, is related to the magnetic flux density B. 50 This means the magnetic flux density in a magnetic field of 5000 A / m.

[0123] In the non-oriented electromagnetic steel sheet of this embodiment, the so-called iron loss W 10 / 400 Lower means that when the plate thickness is 0.26 mm or more, it is below 22.5 W / kg; when the plate thickness is 0.21–0.25 mm, it is below 22.0 W / kg; and when the plate thickness is 0.20 mm or less, it is below 21.5 W / kg. Furthermore, the so-called magnetic flux density B... 50 "Higher" means that when the plate thickness is 0.26mm or more, it is 1.64T or more; when the plate thickness is 0.21-0.25mm, it is 1.63T or more; and when the plate thickness is less than 0.20mm, it is 1.62T or more.

[0124] 6. Mechanical properties

[0125] The non-oriented electromagnetic steel sheet of this embodiment has high strength. While there is no particular limitation on tensile strength, it is preferable that the tensile strength is 650 MPa or more. More preferably, it is 660 MPa or more, and even more preferably, it is 670 MPa or more. Similarly, there is no particular limitation on yield stress, but it is preferable that the yield stress is 550 MPa or more, more preferably 560 MPa or more, and even more preferably 570 MPa or more. Here, tensile strength and yield stress are determined by performing a tensile test in accordance with JIS Z 2241:2022. Furthermore, regarding yield stress, if an upper yield point is clearly generated, the upper yield point is taken as the yield stress. If an upper yield point is not generated, 0.2% of the yield strength is taken as the yield stress.

[0126] 7.Plate thickness

[0127] In the non-oriented electromagnetic steel sheet of this embodiment, from the viewpoint of reducing manufacturing costs associated with cold rolling and final annealing, the thickness of the base material is set to 0.10 mm or more. On the other hand, from the viewpoint of reducing iron loss, the thickness of the base material is set to 0.30 mm or less. Therefore, the thickness of the base material of the non-oriented electromagnetic steel sheet of this embodiment is 0.10 to 0.30 mm. The thickness of the base material is preferably 0.15 to 0.27 mm.

[0128] 8. Insulating film

[0129] In the non-oriented electromagnetic steel sheet of this embodiment, it is preferable that an insulating film is provided on the surface of the base material. Since the non-oriented electromagnetic steel sheet is used after being stacked from punched core blanks, eddy currents between the sheets can be reduced by providing an insulating film on the surface of the base material, and eddy current losses can be reduced as a core.

[0130] There are no particular limitations on the type of insulating film; any known insulating film used as an insulating film for non-oriented electromagnetic steel sheets can be used. Examples of such insulating films include composite insulating films that are primarily inorganic but also contain organic materials. Here, a composite insulating film refers, for example, an insulating film primarily composed of at least one of inorganic materials such as metal chromate salts, metal phosphate salts, colloidal silica, Zr compounds, or Ti compounds, and in which fine particles of organic resin are dispersed. In particular, from the viewpoint of reducing the environmental burden during manufacturing, which has been a growing demand in recent years, insulating films using coupling agents of metal phosphate salts, Zr, or Ti, or their carbonates or ammonium salts as starting materials, are preferred.

[0131] The amount of insulating film applied is not particularly limited, but it is preferred, for example, to be 200–1500 mg / m² per single side. 2 More preferably, it is set at 300–1200 mg / m² per single surface. 2 By forming the insulating film with an adhesion amount within the aforementioned range, excellent uniformity can be maintained. Furthermore, when measuring the adhesion amount of the insulating film afterward, various known measurement methods can be used, such as methods that measure the mass difference before and after immersion in sodium hydroxide aqueous solution, or fluorescence X-ray methods using standard curves.

[0132] 9. Manufacturing method

[0133] The non-oriented electromagnetic steel sheet of this embodiment is not particularly limited in terms of manufacturing method, but for steel ingots having the above-described chemical composition, it can be manufactured, for example, by sequentially performing a hot rolling process, a hot-rolled sheet annealing process, a descaling process, a cold rolling process, and a final annealing process under the conditions shown below. Furthermore, if an insulating film is formed on the surface of the base material, the insulating film forming process is performed after the aforementioned final annealing process. Each process will be described in detail below.

[0134] <Hot Rolling Process>

[0135] A steel ingot (slab) having the above-mentioned chemical composition is heated, and the heated steel ingot is hot-rolled to obtain a hot-rolled plate. There are no particular specifications for the heating temperature of the steel ingot during hot rolling, but for example, it is preferably set to 1050–1250°C. Furthermore, there are no particular specifications for the thickness of the hot-rolled plate, but considering the final thickness of the base material, for example, it is preferably set to approximately 1.5–3.0 mm.

[0136] <Hot-rolled sheet annealing process>

[0137] Then, hot-rolled sheet annealing is performed to reduce iron loss in the steel sheet. For hot-rolled sheet annealing, a continuous annealing furnace is preferred, as it offers higher productivity and produces a more homogeneous metal microstructure compared to batch annealing. Furthermore, as mentioned above, when the Si content in the steel sheet is high and a reduction in sheet thickness is required to decrease iron loss, it is preferable to lower the soaking temperature during hot-rolled sheet annealing. Therefore, hot-rolled sheet annealing is performed at a soaking temperature of 800–920°C for a soaking time of 1 second to 10 minutes. For good magnetic properties, a temperature of 820°C or higher is preferred. For good toughness, a temperature of 900°C or lower is preferred.

[0138] <Oxide Descaling Process>

[0139] For the steel sheet after hot-rolled annealing, pickling is performed after shot peening to remove the oxide scale layer formed on the surface of the base material. The oxide scale layer is well-developed during hot-rolled annealing; therefore, by performing shot peening before pickling, descaling based on the subsequent pickling becomes easier. Here, the pickling conditions, such as the concentration of the acid used for pickling, the concentration of the pickling accelerator used for pickling, and the temperature of the pickling solution, are not particularly limited and can be set to known pickling conditions.

[0140] <Cold rolling process>

[0141] The steel sheets after descaling are then cold-rolled. In cold rolling, the rolling is performed with a reduction rate that results in a final sheet thickness of 0.10 to 0.30 mm.

[0142] <Final Annealing Process>

[0143] After the aforementioned cold rolling, a final annealing is performed. In the manufacturing method of the non-oriented electromagnetic steel sheet of this embodiment, a continuous annealing furnace is preferably used for the final annealing. In the final annealing process, after heating to a temperature of 850°C or higher and less than 900°C, cooling is performed such that the holding time at 850°C or higher is 20 seconds or less. Preferably, the atmosphere is a mixture of H2 and N2 with a H2 ratio of 1 to 100 vol% (i.e., H2 + N2 = 100 vol%), and the dew point of the atmosphere is set to -50 to +10°C.

[0144] If the maximum temperature reached in the final annealing process is less than 850°C, the final annealing effect will not be fully achieved, and the magnetic properties will deteriorate, which is not preferable. On the other hand, if the maximum temperature reached is above 900°C, the strength will be insufficient. Furthermore, if the holding time at 850°C or above exceeds 20 seconds, the strength will be insufficient.

[0145] In this embodiment, the development of textures detrimental to magnetic properties is suppressed by rapid heating in the final annealing process. Therefore, in the final annealing process, the temperature is raised to 850°C or higher at a heating rate of 400°C / s or higher within a temperature range of 500 to 850°C.

[0146] By setting the heating rate to 400°C / s or higher, the development of textures detrimental to magnetic properties can be suppressed. The heating rate is preferably 800°C / s or higher, more preferably 1000°C or higher. A faster heating rate is better, so there is no need to specifically set an upper limit; however, considering equipment limitations, a heating rate of 2000°C / s or lower is preferred. Furthermore, as described above, magnetic properties can be improved by rapidly heating to a temperature of 850°C or higher. Alternatively, the average heating rate can be set to 1–2000°C / s throughout the entire heating process, including the temperature range below 500°C and the homogenization temperature.

[0147] Furthermore, rapid heating under the aforementioned conditions is difficult with conventional methods such as direct heating via gas combustion, radiant heating tubes, or electric heaters. Therefore, in this embodiment, it is preferable to use electric heating, induction heating, or similar methods.

[0148] <Insulating film formation process>

[0149] Following the final annealing described above, an insulating film forming process is performed as needed. The method for forming the insulating film is not particularly limited; a treatment solution for forming a known insulating film as described below can be used, and the treatment solution can be coated and dried using known methods. Examples of known insulating films include composite insulating films that are primarily inorganic and also contain organic materials.

[0150] Composite insulating films, for example, refer to insulating films primarily composed of metal salts such as chromate and phosphate, or inorganic substances such as colloidal silica, Zr compounds, and Ti compounds, and containing finely dispersed organic resin particles. In particular, from the perspective of reducing the environmental burden of manufacturing, which has seen a surge in demand in recent years, insulating films using coupling agents of metal phosphate, Zr, or Ti as starting materials are preferred, as are insulating films using carbonates or ammonium salts of coupling agents of metal phosphate, Zr, or Ti as starting materials.

[0151] Alternatively, the surface of the base material to which the insulating film is formed may undergo any pretreatment, such as degreasing based on alkali or pickling based on hydrochloric acid, sulfuric acid, phosphoric acid, etc., before applying the coating solution. Alternatively, the coating solution may be applied to the surface of the base material without performing these pretreatments, in the final annealed state.

[0152] The non-oriented electromagnetic steel sheet of the present invention obtained as described above has low iron loss, high magnetic flux density and high strength, and is therefore preferred as a raw material for either rotor core or stator core.

[0153] The present invention will be described in more detail below through embodiments, but the present invention is not limited to these embodiments.

[0154] Example

[0155] After heating a slab with the chemical composition shown in Table 1 to 1150°C, it was hot-rolled to a final temperature of 850°C and a final thickness of 2.0 mm, and then coiled at 600°C to produce a hot-rolled steel sheet. The resulting hot-rolled steel sheet was then annealed in a continuous annealing furnace under the conditions shown in Table 2. After descaling the steel sheet by shot peening and pickling, it was cold-rolled to produce a cold-rolled steel sheet with the thickness shown in Table 2.

[0156] Furthermore, final annealing was performed under the conditions shown in Table 2 in a mixed atmosphere of H2::20%, N2:80%, and dew point: -30°C. For the final annealing temperature rise, induction heating was used, and the temperature was rapidly increased to the maximum reach temperature shown in Table 2. Then, the temperature was held for 0–1 second, followed by immediate cooling, and the holding time above 850°C was adjusted by controlling this cooling rate. The steel sheet after final annealing was coated with an insulating film composed of aluminum phosphate and an acrylic-styrene copolymer resin emulsion with a particle size of 0.2 μm, and fired at 350°C in atmospheric conditions.

[0157] [Table 1]

[0158]

[0159] [Table 2]

[0160] Table 2

[0161]

[0162] The underlined part indicates that it is outside the scope of the invention.

[0163] #1 heating rate means the rate of heating within the temperature range of 500 to 850°C.

[0164] However, when the temperature reaches less than 850°C, it means the rate of heating within the temperature range of 500°C to the temperature reached.

[0165] #2 means the temperature reached during rapid heating.

[0166] #3 means the holding time is above 850℃.

[0167] For each test material obtained, the average grain size of the base material was measured according to JIS G 0551:2020 "Steel - Microscopic Test Method for Grain Size". Furthermore, Epstein test pieces were extracted from the rolling direction and width direction of each test material, and the iron loss W was measured using the Epstein test based on JIS C 2550-1:2011. 10 / 400 and magnetic flux density B 50 An evaluation was conducted. Additionally, the density of the steel plate was set at 7.65 g / cm³. 3 Magnetic measurements were then performed.

[0168] After chemically grinding the parent material of each test material to a depth of 1 / 4 of the plate thickness from one side surface to the ground surface, the {200}, {110}, {310}, and {211} planes of the α-Fe phase were analyzed using X-ray diffraction. The {111} plane was then calculated based on the orientation distribution functions (ODFs) representing the three-dimensional texture calculated using series expansion. <112> The degree of clustering of orientations.

[0169] Next, JIS No. 5 tensile test pieces were extracted from each test material according to JIS Z 2241:2022, with the length direction aligned with the rolling direction of the steel plate. Then, tensile tests were performed on the test pieces according to JIS Z 2241:2022, and the tensile strength and yield stress were determined.

[0170] The results are shown in Table 2.

[0171] In tests Nos. 1 to 3, 6, 9, 12, 15, 16, 22, 25, 27 and 28 that meet the requirements of this invention, it is found that it has a high tensile strength of 650 MPa or more, and the iron loss W is low. 10 / 400 Lower, magnetic flux density B 50 Relatively high.

[0172] In contrast, in the comparative tests No. 4, 5, 7, 8, 10, 11, 13, 14, 17–21, 23, 24, 26 and 29, the tensile strength was poor, or the iron loss W was low. 10 / 400 Poor, or magnetic flux density B 50It is of poor quality, with significantly deteriorated toughness, making it more difficult to manufacture.

[0173] Specifically, in Test No. 4, the plate thickness was greater than the specified range, resulting in poorer iron loss. In Test No. 5, the S content was higher than the specified range, resulting in increased MnS precipitation and poorer iron loss. In Test No. 7, the combined Sn and Sb content was lower than the specified range, resulting in {111} <112> The concentration of the orientation exceeds the specified range, resulting in poor magnetic flux density.

[0174] In Test No. 8, the combined Sn and Sb content was higher than the specified range, resulting in deteriorated toughness and fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties. In Test No. 10, the Mn content was higher than the specified range, resulting in poor magnetic flux density. In Test No. 11, the Si+Al+0.5×Mn content was lower than the specified range, resulting in poor iron loss and tensile strength. In Test No. 13, the Si+Al+0.5×Mn content was higher than the specified range, resulting in deteriorated toughness and fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties.

[0175] In test No. 14, the heating rate during the final annealing was lower than the specified range, therefore the result was {111}. <112> The concentration of the orientation exceeded the specified range, resulting in poor magnetic flux density. In test No. 17, the rapid heating during final annealing reached a temperature lower than the specified range, therefore the result was {111}. <112> If the density of orientation exceeds the specified range, the magnetic flux density will be poor. In addition, the average grain size will become smaller than the specified range, resulting in poor iron loss.

[0176] In Test No. 18, the Si content was lower than the specified range, resulting in poor tensile strength. In Test No. 19, the Si content was higher than the specified range, leading to deteriorated toughness and fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties. In Test No. 20, the Al content was lower than the specified range, resulting in a smaller average grain size after final annealing and poor iron loss.

[0177] In test No. 21, the homogenization temperature during the annealing of the hot-rolled plate was lower than the specified range, therefore the result was {111}. <112> The degree of orientation aggregation exceeded the specified range, resulting in poor magnetic flux density. In Test No. 23, the soaking temperature during the annealing of the hot-rolled plate was higher than the specified range, thus deteriorating the toughness and causing it to fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties.

[0178] In Test No. 24, the Al content was higher than the specified range, resulting in deteriorated toughness and fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties. In Test No. 26, the holding time above 850°C exceeded the specified range, resulting in poor tensile strength. In Test No. 29, the final annealing temperature was higher than the specified range, the average grain size became larger than the specified range, and the tensile strength was also poor.

[0179] Industrial availability

[0180] As described above, according to the present invention, non-oriented electromagnetic steel sheets with high strength and excellent magnetic properties can be obtained stably at low cost.

Claims

1. A non-oriented electromagnetic steel sheet, wherein the chemical composition of its base material, in mass percent, C: Below 0.0040%, Si: exceeding 3.50% but below 4.50%, Mn: less than 0.60%, Al:0.30~0.90%, P: below 0.030%, S: Below 0.0018%, N: below 0.0040%, Ti: less than 0.0040%, Nb: less than 0.0050%, Zr: less than 0.0050%, V: less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, The total of one or two of Sn and Sb: 0.005% to 0.060%. Remaining components: Fe and impurities. And satisfy the following equation (i), 4.2≤Si+Al+0.5×Mn≤4.9…(i) in, In the above formula, the element symbols represent the content of each element in terms of mass%. The average crystal grain size of the parent material is 10–40 μm. {111} is located at a position 1 / 4 of the plate thickness from the surface of the base material. <112> The degree of aggregation of orientation is below 8.

0. The thickness of the base material is 0.10 to 0.30 mm.

2. The non-oriented electromagnetic steel sheet as described in claim 1, wherein, The tensile strength is above 650 MPa.

3. The non-oriented electromagnetic steel sheet as described in claim 1 or 2, wherein, The surface of the base material has an insulating film.

4. A method for manufacturing a non-oriented electromagnetic steel sheet, comprising the method for manufacturing a non-oriented electromagnetic steel sheet as described in any one of claims 1 to 3, wherein the method comprises, for a steel ingot, the following steps are performed sequentially: a hot rolling process; a hot-rolled sheet annealing process with a soaking temperature of 800–920°C and a soaking time of 1 second to 10 minutes; a descaling process by pickling after shot peening; a cold rolling process to a sheet thickness of 0.10–0.30 mm; and a final annealing process by heating the sheet to a temperature of 850°C or higher but less than 900°C at a heating rate of 400°C or higher within a temperature range of 500–850°C, and then cooling the sheet at a holding time of 850°C or higher for 20 seconds or less. The steel ingot has the following chemical composition: in mass %, C: Below 0.0040%, Si: exceeding 3.50% but below 4.50%, Mn: less than 0.60%, Al:0.30~0.90%, P: below 0.030%, S: Below 0.0018%, N: below 0.0040%, Ti: less than 0.0040%, Nb: less than 0.0050%, Zr: less than 0.0050%, V: less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, The total of one or two of Sn and Sb: 0.005% to 0.060%. Remaining components: Fe and impurities. And satisfy the following equation (i), 4.2≤Si+Al+0.5×Mn≤4.9…(i) in, The element symbols in the above formula represent the content (mass%) of each element.

Citation Information

Patent Citations

  • Non-oriented electrical steel sheet and method for production thereof

    JP2010090474A

  • Non-oriented electromagnetic steel plate

    WO2019017426A1

  • Non-oriented electromagnetic steel sheet

    WO2020091039A1

  • Non-oriented electromagnetic steel sheet and method for manufacturing same

    WO2021210672A1

  • Non-oriented electromagnetic steel plate

    CN110573643A